Non-monotonic dynamic correlation explored via active microrheology - Madanchi, A.; Aghaei, F.; Rahbari, S. H.E.; Reza Rahimi Tabar, M.; Pöschel, Thorsten (Journal of Statistical Mechanics-Theory and Experiment, 2024)
In the study of local and heterogeneous structures in supercooled liquids, microrheology plays a crucial role, offering a closer examination of the mechanical properties at a local level. We concentrate on active microrheology, where an external force drives a probe particle. This technique is employed in the study of a Kob-Andersen mixture, using extensive molecular dynamics simulations. Through active microrheology, we analyze the positional dependence of viscosity, observing how probe particles respond to activation velocity. Utilizing advanced stochastic analysis, we disentangle the deterministic and stochastic components of the local viscosity time series, characterizing its nonlinear and intermittent properties, which indicate heterogeneity. We construct a Langevin equation to model the dynamics of local viscosity and derive its drift and diffusion coefficients from simulation data. Additionally, we investigate the temperature-dependent variations of viscosity dynamics, unveiling their multiplicative and nonlinear nature. We elaborate on how the existence of multiplicative dynamics in viscosity results in the characteristic emergence of heterogeneity within viscosity dynamics. We derive a dynamic correlation length from local viscosity. Moreover, this correlation length shows a non-monotonic dependence on temperature with a maximum at about the Kauzmann temperature.
CRIS-Team Scopus Importer:2024-12-06
Keywords: dynamical processes; glasses (structural); heterogeneous materials; stochastic processes